2007
DOI: 10.1111/j.1551-2916.2007.02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoluminescence of Eu2+‐Doped α‐Silicon Nitride Nanowires Coated with Thin BN Film

Abstract: A feasible doping strategy is introduced to synthesize Eu2+‐doped α‐Si3N4 nanowires coated with a thin BN film. The nanowires were characterized by X‐ray diffraction, scanning electron microscopy, high‐resolution transmission electron microscopy, and a fluorescence spectrophotometer. The Eu2+‐doped α‐Si3N4 nanowires emitted strong yellow light, which is related to the 4f65d–4f7 transition of Eu2+, upon a broad excitation wavelength range between 250 and 450 nm. The obtained nanowires provided a potential candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For example, Eu 2+ is very stable in α-sialon 10 or Si 3 N 4 . 25 Therefore, the oxidation degree of Eu 2+ decreases significantly in the MW-SiN-BAM host lattice, and a highly thermal stability of the MW-SiN-BAM phosphor is thus realized. It was reported that the decrease in the Eu 2+ concentration was accompanied by a decrease in the trap concentration during the oxidation process.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Eu 2+ is very stable in α-sialon 10 or Si 3 N 4 . 25 Therefore, the oxidation degree of Eu 2+ decreases significantly in the MW-SiN-BAM host lattice, and a highly thermal stability of the MW-SiN-BAM phosphor is thus realized. It was reported that the decrease in the Eu 2+ concentration was accompanied by a decrease in the trap concentration during the oxidation process.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Eu 21 is very stable in a-sialon 19 or Si 3 N 4 . 20 These three reasons explain that the degree of Eu 21 oxidation decreases significantly in the SiN-BAM host lattice and the high thermal stability of SiN-BAM. Figure 4 shows the XANES spectra of BAM and SiN-BAM baked at 6001C for 1 h. There are two absorption maxima at 6977 and 6984 eV, which are due to the divalent and trivalent oxidation states of europium, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, the lower electronegativity of N stabilizes Eu 2+ . For example, Eu 2+ is very stable in α‐sialon 19 or Si 3 N 4 20 . These three reasons explain that the degree of Eu 2+ oxidation decreases significantly in the SiN–BAM host lattice and the high thermal stability of SiN–BAM.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, additional nitride-based nanomaterials have been reported in the literature. Some examples, such as BN:Eu 2+ , , GaN:Eu 2+ @SiO 2 , , SiO 2 @CaSi 2 O 2 N 2 :Eu 2+ , CaAlSiN 3 :Eu 2+ , Si 3 N 4 :Eu 2+ @BN, Ca 2 Si 5 N 8 :Eu 2+ ,Tm 3+ , and (Sr,Ba) 2 Si 5 N 8 :Eu 2+ , are shown in Table .…”
Section: Nanostructured Eu2+ Phosphors and Their Optical Propertiesmentioning
confidence: 99%